Gossypium hirsutum Salt Tolerance Is Enhanced by Overexpression of G. arboreum JAZ1 - Zhao, Ge; Song, Yun; Wang, Qianhua; Yao, Dongxia; Li, Dongliang; Qin, Wenqiang; Ge, Xiaoyang; Yang, Zuoren; Xu, Wenying; Su, Zhen; Zhang, Xueyan; Li, Fuguang; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Gossypium arboreum possesses many favourable traits including robust defence against biotic and abiotic stress although it has been withdrawn from the market because of lower yield and fibre quality compared to G. hirsutum (upland cotton). It is therefore important to explore and utilize the beneficial genes of G. arboretum for G. hirsutum cultivar breeding. Here, the function of G. arboreum JAZ1 in tolerance to salt stress was determined through loss-of-function analysis. GaJAZ1can interact with GaMYC2 to repress expression of downstream genes whose promoters contain a G-box cis element, affecting plant tolerance to salinity stress. The experimental data from NaCl treatments and a two year continuous field trial with natural saline-alkaline soil showed that the ectopically overexpressed GaJAZ1 significantly increased salt tolerance in upland cotton compared to the wild type, showing higher growth vigour with taller plants, increased fresh weight, and more bolls, which is due to reprogrammed expression of tolerance-related genes and promotion of root development. High-throughput RNA sequencing of GaJAZ1 transgenic and wild-type plants showed many differentially expressed genes involved in JA signalling and biosynthesis, salt stress-related genes, and hormone-related genes, suggesting that overexpressing GaJAZ1 can reprogram the expression of defence-related genes in G. hirsutum plants to increase tolerance to salt stress. The research provides a foundation to explore and utilize favourable genes from Gossypium species for upland cotton cultivar breeding.